2018
DOI: 10.1111/jfs.12580
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol screening in wheat‐derived products in Gran Asunción, Paraguay

Abstract: Fusarium graminearum is one of the most important pathogens affecting wheat production in Paraguay. This fungus decreases yield and grain quality; the most important consequence is the production of mycotoxins from the trichothecene group, secondary metabolites toxic to humans and other animals. The toxin reported in Paraguay is deoxynivalenol, which has effects on the gastrointestinal tract and immune system. To determine the presence of deoxynivalenol in flour and baked goods, samples of wholemeal flour and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…At present, at least 100 countries have mandatory limits on DON levels in food and feed. In view of its serious toxic effects, in the preliminary draft of the DON maximum levels (MLs), the Codex Alimentarius Food (FAO) Committee recommended the following limits: 2 mg/kg in unprocessed cereals, 1 mg/kg in semi-processed products using wheat, corn and barley as raw materials, and 0.5 mg/kg in cereals for infants and young children [10,11]. In China, the ML of DON in maize, wheat, and their products is regulated at 1 mg/kg [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…At present, at least 100 countries have mandatory limits on DON levels in food and feed. In view of its serious toxic effects, in the preliminary draft of the DON maximum levels (MLs), the Codex Alimentarius Food (FAO) Committee recommended the following limits: 2 mg/kg in unprocessed cereals, 1 mg/kg in semi-processed products using wheat, corn and barley as raw materials, and 0.5 mg/kg in cereals for infants and young children [10,11]. In China, the ML of DON in maize, wheat, and their products is regulated at 1 mg/kg [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Four studies have been reported in Paraguay, including wheat, beer, wine, milk, and milk formulas. The first described DON in wheat flour, bread, and crackers found high levels in most manufactured food (crackers, 0.038 ± 0.049 ng/g) (Arrua Alvarenga et al, 2019a). Furthermore, Arrua Alvarenga et al (2019b) reported 25% OTA in wine and 24% of DON in beer.…”
Section: Paraguaymentioning
confidence: 98%
“…Un grave problema asociado a la seguridad alimentaria es la contaminación con hongos filamentosos y sus micotoxinas. Esto puede darse como consecuencia de la presencia de patógenos como Penicillium sp., Fusarium sp., Aspergillus sp., que pueden afectar a los cultivos tanto en condiciones de campo y/o almacenamiento (1)(2)(3)(4) .…”
Section: Introductionunclassified